1995
DOI: 10.1111/j.1600-051x.1995.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid demineralization of cementum and dentin: the effect of application pressure

Abstract: Previous work has shown that a 25-30% citric acid solution was the most effective concentration with which to demineralize dentin. The purpose of this investigation was to study the topography, using a scanning electron microscope, of root surfaces treated with a 30% citric acid solution using various application pressures. 20 freshly extracted human teeth were collected and stored in physiologic saline at room temperature. 3 root specimens, approximately 3x5x5 mm in size, were prepared from the coronal period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…3). These results are in agreement with those of previous studies (17,18), which described considerable changes in surface morphology after burnishing with citric acid.…”
Section: Discussionsupporting
confidence: 93%
“…3). These results are in agreement with those of previous studies (17,18), which described considerable changes in surface morphology after burnishing with citric acid.…”
Section: Discussionsupporting
confidence: 93%
“…These include fibronectin binding, fibroblast chemotaxis and proliferation, all of which lead to a more stable clot formation that is resistant to epithelial migration. 1,5,6 It was observed that both the demineralizing solutions produced fibril tufting (Fig. 6), in an average graded scale of one which is in support of the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…5 As observed in the present study EDTA appears to be effective in promoting the process by providing the increased surface area.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Samples in the groups II, III, IV and V were conditioned during 3 minutes and solutions were renewed every 30 seconds. [18][19][20] After the conditioning procedure samples were washed with 10 ml of saline solution.…”
Section: Conditioning Proceduresmentioning
confidence: 99%